A Humanless World: The Progressive Artificial Intelligence and its Impact on Intellectual Property - Dinev, Kaloyan Dinkov (Kent Law Review, 2018)
With recent leaps in the field of robotics and artificial intelligence, the boundary between science fiction and reality is blurring constantly, with computers performing actions previously thought to be unique only to man. Though challenged by traversal of the physical realm, their capabilities to mimic human problem solving and creativity is growing exponentially. In discovering this potential lies the possibility of a cultural and scientific enrichment the likes of which will dwarf both the Renaissance and the Industrial Revolution, respectively. Naturally this is accompanied by countless inventions and artistic expressions from which society will inevitably benefit. However, due to their originators likely being at least in part or wholly computers, the question will arise as to who will be their true owners or authors from a legal standpoint. This article will examine the extent to which human and machine intelligence can be compared and will attempt to ascertain the ways in which the latter could pose a threat to the system of Intellectual Property laws in place to protect the rights of inventors/creators. Where possible, the piece will also attempt to propose potential remedies and pre-emptive actions to alleviate the dangers such a synthetic revolution could cause to IP’s legal framework.